PERLINDUNGAN HUKUM BAGI ISTRI DAN ANAK DALAM PERKAWINAN ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA TANPA IZIN ATASAN (STUDI DI POLRESTABES MEDAN) - HIDAYATI ZAHRA BAHRI (PREMISE LAW JURNAL, 2017)
ABSTRACT The Indonesian police officers as state’s apparatus have to comply with the prevailing legal provisions, especially a marriage conducted by an Indonesian police officer has to follow Marriage Law and the other regulations imposed on the Police Force. One of the requirements for getting marriage, before registering it to the Religious Affairs Office and the Civil Registry Office, is getting permission from the superiors. Police officers and government employees who work for the Police Force have to report to their superiors in written form when they want to get married. Without the acknowledge of their superiors, they will be considered as being single and their wives and children will not get any allowance; in other words, they are considered as having no dependent. A marriage without getting permission in the Police Force has an effect on a police officer’s wife and children in which they are legally protected by Law on Marriage and Law on Child Protection. The result of the research showed that the decision of the Disciplinary Infraction Meeting was considered correct in imposing punishment on police officers who violated the Government Regulation No. 2/2003 on Disciplinary regulation on the Indonesian Police Officers. Keywords: Wife, Child, Police Officer’s Marriage, Permission from Superior